Discourse on Splits in Nepal’s Communist Movement: An Ontological Perspective - Puri, Ram Prakash (HISAN: Journal of History Association of Nepal, 2025)
This study explores the discourse of factionalism within Nepal’s communist movement through an ontological perspective. Communism in Nepal, rooted in Marxist-Leninist philosophy, has historically emphasised proletarian and peasant struggles but has experienced persistent splits due to divergent ideological, organisational, and strategic orientations. Ontology is applied to identify what each party regards as “real”-whether class struggle, parliamentary democracy, or state power-and how these perceptions shape their minimum programs, maximum goals, and political strategies. The analysis shows that parties such as NCP (Mashal), NCP (ML), and RCP Nepal prioritise proletarian leadership and view armed struggle as a long-term necessity, while UML, Maoist Centre, and Unified Socialist emphasize constitutional processes and peaceful competition. The Nepal Workers and Peasants Party (NWPP) maintains a focus on proletarian struggle and the socialization of production. Despite differences, all affirm socialism and communism as ultimate goals. Factionalism thus emerges not as incidental but as a dialectical outcome of ontological contradictions-class, ideology, and organizational practice-within the broader trajectory of Nepal’s communist movement.